Relative Economics & Mahaveer’s Concepts for Planning and Policy Making - Kumar Jain, Trilok (Journal of Advanced Research in Economics and Business Management, 2023)
This is a conceptual paper on the present economic policies and on the fundamentals of relative economics. This paper is intended to promote a wholistic thinking and a broader framework for our development. The author looks at some of the important ideas of scholars relating to economic planning and development. The author reviews ideas like Environmental Economics, Ecological Economics, Gram Swarajya. The author proposes that there is a need of a fresh thinking about developmental yardsticks. This paper explores the profound ideas of Mahaveer, a visionary figure in Indian civilization, whose principles emphasize restraint on consumption and advocate for a holistic approach to economic planning. In contrast to contemporary economists who prioritize material wealth and consumption, Mahaveer’s teachings, reintroduced by Acharya Maha Pragya through Relative Economics, provide a framework for achieving sustainable development goals. Relative Economics extends economic indicators beyond mere material resources, urging a comprehensive assessment of development based on broader parameters, impact on overall happiness, consideration of other living beings, and the long-term survival of the planet. The consequences of such planning manifest in environmental degradation, species endangerment, and a growing disconnect from traditional values rooted in non-violence and nature-centric economic systems. The paper concludes by stressing the urgency of reevaluating current developmental plans. It advocates for a shift from exclusive reliance on traditional economic indicators like GDP to broader measures such as human development indicators, emphasizing the need for balanced and sustainable development that prioritizes overall well-being, equity, and environmental preservation. In this context, Relative Economics emerges as a compelling framework that aligns with the principles of Mahaveer and offers a pathway to a more inclusive and sustainable future.